2005
DOI: 10.1007/bf02504688
|View full text |Cite
|
Sign up to set email alerts
|

An exposition of the crucial issues in China's educational informatization

Abstract: An Upsurge in WAN EducationWAN is a computer network that spans a relatively large geographical area. Typically, a WAN consists of more than two local area networks (LANs). These are often connected through public networks, such as the fiber system, leased data lines, or satellites. The Internet, for example, is the largest WAN in existence. From 2002 to 2004, China constructed branches of WAN educational network (WEN) throughout metropolitan areas such as Beijing, Shanghai, Shenzhen, Foshan, Dongguan, and Gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…No matter what tools they used to communicate, American students found it easy to communicate online; Korean students were most hindered by online communication, possibly because of their cultural perceptions on electronic communications as impersonal and even impolite (Kwon & Danaher, 2000). Chinese students, who typically grew up in noninteractive learning environments (Yu, 2002; Yu et al , 2005), found online broadcast with no interaction to be the most comforting way of learning. Some even expected online learning to be similar to the conduct of traditional classrooms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No matter what tools they used to communicate, American students found it easy to communicate online; Korean students were most hindered by online communication, possibly because of their cultural perceptions on electronic communications as impersonal and even impolite (Kwon & Danaher, 2000). Chinese students, who typically grew up in noninteractive learning environments (Yu, 2002; Yu et al , 2005), found online broadcast with no interaction to be the most comforting way of learning. Some even expected online learning to be similar to the conduct of traditional classrooms.…”
Section: Resultsmentioning
confidence: 99%
“…The researcher selected online courses from these institutions primarily because of the pedagogic and cultural contrasts of the three nations (Kwon & Danaher, 2000). For example, the pedagogy for distance education in the US is increasingly more focussed on interactive and student‐centred learning (Kwon & Danaher, 2000), but online courses offered in China and South Korea often feature teacher‐centred presentation and students’ silent note taking (Yu, Wang & Che, 2005). Table 1 in displays the dimensions of cultural variability among the three nations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adnan and Anwar (2020) believed that many students in Pakistan cannot access the Internet due to technologies as well as economic limitations. China also faces similar problems, students in Chinese rural areas where family social economic status are generally not compared to those in cities, lack of facilitating conditions such as poor Internet connection and mobile learning tools may constitute great barriers to students' mobile learning intentions (Yu, Wang & Che, 2005). Although first-order barriers such as technology access (Ertmer, 1999) are losing their importance in developed countries, they still remain critical for people in underdeveloped rural areas.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…For instance, the project needs to build up a service market under the guidance of local governments, so that these skilled experts or change agents can receive reasonable financial compensations for their important work. A fully functioning market can create a steady flow of distance‐education experts from the cities to the countryside, not the other way around (Yu et al . 2005).…”
Section: Problems and Reflectionsmentioning
confidence: 99%